1999
DOI: 10.1038/sj.mp.4000558
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the promoter region of monoamine oxidase-A gene and mood disorders

Abstract: A polymorphism of a variable number tandem repeat (VNTR), that was recently found in the promoter region of the monoamine oxidase-A (MAOA) gene, was shown to be associated with its transcriptional activity. This study examined whether this functional polymorphism of the MAOA gene is associated with the risk of developing mood disorders in a Japanese sample of 161 patients with bipolar disorder, 98 with unipolar depression, and 258 controls. There was no significant genotypic or allelic association, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 6 publications
8
46
2
1
Order By: Relevance
“…In addition, the MAOA-LPR has been associated with bipolar disorders particularly in females (Ho et al, 2000), and with suicide in depressed males (Du et al, 2002), whereas other studies failed to detect association with suicidal behavior in mood disorders (Kunugi et al, 1999;Kirov et al, 1999;Syagailo et al, 2001;Ono et al, 2002). Although not consistently replicated (Craddock et al, 1995;Nothen et al, 1995), various other MAOA variations were found to influence addictive behavior (Parsian et al, 1995;Vanyukov et al, 1995;Hsu et al, 1996;Gade et al, 1998) and the risk for affective und anxiety disorders (Schulze et al, 2000;Deckert et al, 1999;Furlong et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the MAOA-LPR has been associated with bipolar disorders particularly in females (Ho et al, 2000), and with suicide in depressed males (Du et al, 2002), whereas other studies failed to detect association with suicidal behavior in mood disorders (Kunugi et al, 1999;Kirov et al, 1999;Syagailo et al, 2001;Ono et al, 2002). Although not consistently replicated (Craddock et al, 1995;Nothen et al, 1995), various other MAOA variations were found to influence addictive behavior (Parsian et al, 1995;Vanyukov et al, 1995;Hsu et al, 1996;Gade et al, 1998) and the risk for affective und anxiety disorders (Schulze et al, 2000;Deckert et al, 1999;Furlong et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning suicide the results are not convincing as no association was identified for the MAOA uVNTR variant and only a weak association (P = 0.016) of the Fnu4HI locus with a history of suicide attempts in female bipolar patients, but not in males. 159 Further studies failed to find an association between suicidality and the MAO uVNTR in heroindependent subjects of Italian descent, 160 in Japanese unipolar and bipolar patients 159,161,162 or Japanese suicide victims. 162 Only in the study by Du et al 163 a positive result with the MAOA gene was observed.…”
Section: Monoamine Oxidase Amentioning
confidence: 99%
“…2ª-Repetição polimórfica na região promotora do gene codificando a monoaminooxidase A (MAO-A) que Lim et al (1995) relataram estar associada ao transtorno bipolar, no que foram replicados por Preisig et al (2000), embora relatos negativos também existam (Kunugi et al, 1999).…”
Section: Estudos De Associaçãounclassified